2017
DOI: 10.1016/j.idcr.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The first case of recurrent ultra late onset group B streptococcal sepsis in a 3-year-old child

Abstract: Group B streptococcus (GBS) is a commonly recognized cause of sepsis and meningitis in neonatal and young infants. Invasive GBS infection is classified into early onset GBS disease (EOD, day 0–6), late onset GBS disease (LOD, day 7–89) and ultra late onset GBS disease (ULOD, after 3 months of age). ULOD is uncommon and recurrence is especially rare. We present the first recurrent case of ULOD GBS sepsis in 3-year-old girl with a past medical history of hydrops fetalis and thoracic congenital lymphatic dysplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The invasive GBS infections can be categorized into early-onset disease (EOD), late-onset disease (LOD), and rarely as ultra-late onset disease (ULOD). The EOD occurs within the first six days of life while the LOD and the ULOD occurs from 7 up to 89 days, and after 3 months of age respectively [ 6 , 7 ]. Recently, GBS has emerged as a leading cause of meningitis in neonates and young infants, resulting in high mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The invasive GBS infections can be categorized into early-onset disease (EOD), late-onset disease (LOD), and rarely as ultra-late onset disease (ULOD). The EOD occurs within the first six days of life while the LOD and the ULOD occurs from 7 up to 89 days, and after 3 months of age respectively [ 6 , 7 ]. Recently, GBS has emerged as a leading cause of meningitis in neonates and young infants, resulting in high mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Other reports include a child with steroid-responsive nephrotic syndrome 8 and recurrent invasive GBS disease in a child with thoracic congenital lymphocytic dysplasia. 9 Human immunodeficiency virus infection has been associated with GBS disease but usually presents earlier than 1 year. 4,10 Such reports support evaluation of components of the immune system that modulate host defense in children with invasive GBS disease.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] GBS infection is rare in children over 1 year of age. [ 16 18 ] Phares et al [ 17 ] reported that the incidence of invasive GBS infection in the United States was 0.22 per 100,000 in children aged 1 to 14 years compared with 7.2 per 100,000 in the total population. Additionally, 40% of GBS-infected patients aged 1 to 14 years had at least 1 underlying disease, such as a neurologic disorder, immunosuppression, asthma, malignancy, or renal disease.…”
Section: Discussionmentioning
confidence: 99%